DETERMINING THE INTERMEDIATION EFFECT OF BRAND TRUST ON THE RELATIONSHIP OF BRAND IMAGE AND BRAND LOYALTY ON THE FORMATION OF CONSUMER PREFERENCES (Third Sector Social Economic Review, 2022)
In today's competitive environment, organizations try to differentiate from their competitors by using the power of branding in order to be successful in marketing communications. Those who achieve a strong brand position are those who have a distinctive and positively formed brand image in consumer memories, have brand trust by proving that they fulfill their promises and take care of customer interests, and contribute to the formation of brand loyalty between the product and the customer through these components. In this context, a conceptual model has been developed through the Structural Equation Model (SEM) in order to detect this effect. For this purpose and within the framework of the model, the survey was conducted with 414 white goods users living in Nazilli, by means of convenience sampling method. Analysis of the data was carried out using SPSS 22.0/AMOS 22.0 package programs. Confirmatory factor analysis, frequency analysis and structural equation modeling were used throughout the research. As a result of the research, it was determined that the goodness of fit indices of the created model were at an acceptable level, and the hypotheses formed by finding the significant and positive effects of brand image and trust on brand loyalty were accepted.
Keywords: Brand Image; Brand Trust; Brand Loyalty; Confirmatory Factor Analysis; Structural Equation Model